The language of genders in the "Labour of Love" / Suzana Ab. Rahim - Ab. Rahim, Suzana (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2005)
This paper is based on Lakoff's conviction that there are certain features that exist in the language used by a certain gender. The paper aims to look at the ways selected men and women converse in the video clip "Labour of Love" and to analyse whether the existing patterns as claimed by Lakoff do occur in the conversations ensued. The results of the study revealed that hedges or back channel support were frequently used in these conversations, making it a dominant feature in their utterances. Apart from that, redundancy and "empty" adjectives were also observed as featured in the dialogues among the non-native English Language speakers selected.